EDUKASI ANTI BULLIYING UNTUK MENINGKATKAN KESADARAN SISWA DI SD NEGERI 1 MANGGARWETAN KECAMATAN GODONG - Mika Agustiana; Christina Nur Widayati; Fatchulloh; Leli Rezky Dwi Oktavia; Anita Lufianti; Yuwanti; Rahmawati; Yesita Ragil Kusumaningrum; Fitriani (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2026)
Background: Bullying among children often involves repeated aggressive behavior by an individual or group against others perceived as weak and unable to defend themselves. Using force to verbally hurt a person or group of people, or to demean others, can have significant impacts on the victim, ranging from physical harm to difficulty interacting with others socially. Purpose: This community service activity aims to raise awareness about anti-bullying behavior in elementary schools, its negative effects, and the importance of tolerance among children. Method: This community service activity was implemented using counseling methods through lectures, discussions, and role-playing simulations to provide a realistic picture and effective ways to prevent bullying among elementary school students. Results: This activity resulted in increased participant understanding of the impact of bullying and simple, effective steps to prevent it. Conclusion: The community service activities that have been carried out have contributed to creating a safer elementary school atmosphere for children and supporting their mental well-being.